Ultrastructural characteristics of erythroid cells in congenital dyserythropoietic anemia type II, with a focus on peripheral cisternae and double membranes - Yong-Xin Ru; Shu-Xu Dong; Jing Liu; Brian Eyden (Blood Science, 2023)
Peripheral cisternae and double membranes (PCDMs) in erythroid cells are a landmark of type II congenital dyserythropoietic anemia (CDA). To gain further insights into the mechanism of dyserythropoiesis, erythroblasts and erythrocytes in bone marrow were studied in 22 Chinese patients with CDA Ⅱ by transmission electron microscopy. The study demonstrated an increase in all patients in erythroblasts with PCDMs with development from pro-erythroblast to red blood cells. PCDMs often connected with cisternae of endoplasmic reticulum (ER) and the perinuclear space, and were accompanied by karyopyknosis, karyolysis and disruption in polychromatic and orthochromatic erythroblasts. The results suggest that PCDMs are transformed from ER during erythropoiesis and participate in the dissolution and deletion of late erythroid cells in patients with CDA II.